The Television Existence in the Age of on-Demand Video Streaming - Hery Setiawan; Pawito Pawito; Andrik Purwasito (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
Television is a favorite mass media for some people; even watching television has become a mandatory ritual. Indeed, television shows have an impact on viewers. As technology develops and advances, television conditions change. This study aims to examine the current pattern of television use in Karanganyar City, Indonesia, in the era of popularity and increasing use of on-demand video streaming. This research is descriptive quantitative research. The research method used is a questionnaire survey, and the analysis was done using descriptive statistics. The results showed that the audience chose to watch television to seek information and entertainment. However, the Karanganyar audiences are not included in the heavy audience category. Their favorite programs are drama and news. For this reason, television programs must be educational and informative. The television must conduct a thorough evaluation so that other media do not drown out the use of television.